Improving the Management of the Number and Composition of Buses in the City of Fergana - Maxammadjon Qobulov (Genius Journals, 2022)
It is necessary to systematically organize transportation services for passengers in the city of Fergana. There are few bus routes in the city of Fergana due to the lack of proper selection of vehicles to provide transport services to the population, development of bus transport services in densely populated areas and quality implementation of transport services to the population. This is one of the pressing issues today
Keywords: Bus route; traffic flow; traffic structure; intercity transportation